Flexibility versus Rigidity: How Conformational Constraint, Steric Hindrance and Solvent Impact Binding between π‐Electron Poor Tweezer‐Type Hosts and π‐Electron Rich Guests. Issue 10 (13th February 2023) - Panther, Lydia A.; Stankunaite, Monika; Sharma, Manvendra; Spencer, John; Greenland, Barnaby W.
Abstract: Tweezer‐type receptors that form π−π stacked supramolecular complexes are important components in functional polymeric materials and molecular machines. Herein, we study how varying specific structural components of tweezer‐receptors impacts their binding. A library of tweezer receptors, each containing two π‐electron poor receptor residues and differing by the nature of the linking unit which was either a flexible 2, 2′‐(ethylenedioxy)bis(ethylamine) residue or a rigid 3, 3''‐diamino‐ m ‐terphenyl diamine structure, were synthesised. Each tweezer formed 1 : 1 supramolecular complexes with π‐electron rich residues (1, 5‐dihydroxynapthalene and pyrene) as confirmed by UV/Vis and 1 H NMR spectroscopic studies. Binding constants were determined to be between 2.3×10 −5 and 71 M −1 in organic solvents and were one magnitude greater in aqueous solvents for water soluble systems. The nature of the linker had variable effects on the binding constants, showing the design of tweezer type supramolecular receptors with targeted K a values is non‐trivial and requires structural optimisation supported by binding constant determination studies. Abstract : In this work, we studied how varying specific structural components of tweezer‐receptors impacts their binding. A library of tweezer receptors, each containing two π‐electron poor receptor residues and differing by the nature of the linking unit, were synthesised. Each tweezer formed supramolecular complexes with π‐electron rich residue pyrene, confirmed by UV/Vis and 1 H NMR spectroscopic studies. The nature of the linker had variable effects on the binding constants.